Models and references that influence gender stereotypes in STEM: a case study in Spain - Verdugo-Castro, Sonia; García-Holgado, Alicia; Sánchez-Gómez, Mª Cruz; García-Peñalvo, Francisco José (Revista de Investigación Educativa, 2025)
The science, technology, engineering, and mathematics (STEM) sector is an academic and professional field with high gender disparity figures despite being a field with a low unemployment rate. The “Questionnaire with University Students on STEM Studies in Higher Education” (QSTEMHE) was designed to determine the opinion of the Spanish university population on all branches of knowledge about gender stereotypes in STEM studies. This validated instrument was applied to a university sample of 2101 people from different Spanish universities. A quantitative methodology and the non-experimental ex-post-facto method were used, employing a simple random sampling technique. This study aims to analyse the relationship established between the models and references that university students have had and their manifestation of gender stereotypes on the ability to perform in STEM higher education studies. Among the main results, gender stereotypes about STEM degrees persist, considering them masculinised and male-oriented. Furthermore, the study confirms that models and references taken into account when choosing higher education studies impact the perception of men and women regarding stereotypes in STEM.